Bay’ al wafa (Sale with a promise to buy back at face value) and its contemporary implementations - Mohamed Cherif, Benaouali; Mohd Noor, Azman (International Journal of Al-Turath In Islamic Wealth and Finance, 2023)
This study aims to shed light on Bay’ al wafa (Sale with a promise to buy back at face value) and its contemporary implementations. Some Islamic financial institutions deal with it in some of their products. The jurists differ about its permissibility, traditional and contemporary, due to the variance of its forms in the eyes of Islamic schools of jurisprudence and the absence of explicit text from the Qur’an or the Sunnah regarding it. Therefore, this research attempts to shed light on the reality of bay’ al wafa’ through its concept, modes and contemporary applications, by addressing the views of the contemporary scholars and their supporting evidences. This research concluded that the Sale with a promise to buy back at face value is one of the fictitious transactions, where the buyer is required to fulfil the return of the item to the seller when the seller returns the price to him. It appears to be a collateral in the form of a sale, and it contravenes the requirements of the sale contract and its ruling which transfers the ownership on permanent basis.